Biosorption of Copper in Swine Manure Using Aspergillus and Yeast: Characterization and Its Microbial Diversity Study - Zhen, Yongkang; Wang, Mengzhi; Gu, Yalan; Yu, Xiang; Shahzad, Khuram; Xu, Jun; Gong, Yuqing; Li, Peizhen; Loor, Juan J. (Frontiers in Microbiology, 2021)
Dietary copper supplementation in the feed of piglets generally exceeds 250-800 mg/kg where a higher quantity (>250 mg/kg) can promote growth and improve feed conversion. Despite the reported positive effects, 90% of copper is excreted and can accumulate and pollute the soil. Data indicate that fungi have a biosorptive capacity for copper. Thus, the objectives of the present experiment were to study the effects of adding different strains of fungi on the biosorptive capacity for copper in swine manure, and to evaluate potential effects on microbiota profiles. Aspergillus Niger (AN), Aspergillus oryzae (AO) and Saccharomyces cerevisiae (SC) were selected and each added at 0.4% into swine manure which containing 250 mg/kg of copper. The incubations lasted for 29 days, biosorption parameters were analyzed on the 8th (D8), 15th (D15), 22nd (D22) and 29th (D29) day. Results showed that after biosorption, temperature was 18.47-18.77 °C, pH was 6.33-6.91, and content of aflatoxin B1, ochratoxin A and deoxynivalenol were low. In addition, residual copper concentration with AN was the lowest on D15, D22 and D29. The copper biosorption rate was also highest with AN averaging 84.85% on D29. Biosorption values for AO reached 81.12% and for SC were lower than 80%. Illumina sequencing of 16S and ITS rRNA gene revealed that fungal treatments reduced the diversity and richness of fungal abundance, but had no effect on bacterial abundance. Unknown_Marinilabiliaceae, Proteiniphilum, Tissierella and Curvibacter were the dominant bacteria while Aspergillus, and Trichoderma. were the dominant fungi. However, the added strain of S. cerevisiae was observed lower to be the dominant fungi which contained less than 0.05%. The KEGG pathway enrichment predicted via PICRUSt2 indicated there were bacterial genes potentially related to various aspects of metabolism and environmental information processing. Overall, data indicated that Aspergillus can provide microbial materials for adsorption of copper.